2018
DOI: 10.1111/jch.13351
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of angiotensin II type‐1 receptor antibodies in primary aldosteronism and further considerations about their possible pathogenetic role

Abstract: Angiotensin II type-1 receptor autoantibodies (AT1RAb) have been involved in the genesis of primary aldosteronism (PA), both in aldosterone-producing adenoma (APA) and in idiopathic hyperaldosteronism (IHA). In this study, we evaluated the titer of AT1RAb in 44 PA patients (15 with APA and 29 with IHA) compared with 18 normotensive healthy controls who were matched for gender and age. In 17 PA patients (6 APA and 11 IHA) the titer was evaluated under mineralocorticoid receptor (MR) antagonist treatment. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
2
10
0
2
Order By: Relevance
“…If spironolactone is not associated with HCs, barrier contraceptives are necessary during the treatment given the potential fetal toxicity of its antiandrogen action; canrenone and potassium canrenoate have a weak antiandrogen activity, but that can still disturb the sexual development of a male fetus; only eplerenone is devoid of antiandrogen activity, but isolate reports about its use in pregnancy are reported, requiring further studies . Recently, the presence of autoantibodies stimulating the angiotensin II type 1 receptor has been reported in preeclampsia and in primary aldosteronism, supporting the role of RAAS in the pathogenesis of these conditions().…”
mentioning
confidence: 76%
“…If spironolactone is not associated with HCs, barrier contraceptives are necessary during the treatment given the potential fetal toxicity of its antiandrogen action; canrenone and potassium canrenoate have a weak antiandrogen activity, but that can still disturb the sexual development of a male fetus; only eplerenone is devoid of antiandrogen activity, but isolate reports about its use in pregnancy are reported, requiring further studies . Recently, the presence of autoantibodies stimulating the angiotensin II type 1 receptor has been reported in preeclampsia and in primary aldosteronism, supporting the role of RAAS in the pathogenesis of these conditions().…”
mentioning
confidence: 76%
“…Recent studies have shown an important role of autoimmunity in primary hyperaldosteronism, preeclampsia, and other autoimmune diseases. 7 , 8 The association between autoimmunity and hypertension has been considered in previous works especially considering that aldosterone is the main pro‐inflammatory and autoimmunity‐inducing hormone. Recently, it has been shown that in inflammatory diseases, the aldosterone‐renin ratio is often higher than in healthy controls, as for example in polycystic ovary syndrome.…”
Section: Autoimmunity Angiotensin 2 Type 1 Receptors and Aldosteronementioning
confidence: 99%
“…Another interesting hypothesis of the pathogenesis of PE was postulated by Wallukat et al (36), who firstly described in preeclamptic women the presence of AT1-AA, which were able to induce a preeclamptic state when injected in pregnant mice (37). The subsequent discovery of increased titers of AT1-AA even in PA patients (22) leads to a possible common underlying etiopathogenesis of PE and PA. The possible pathogenetic role of AT1-AA is complex and could be related to the activation of AT1 receptor, leading to increased vascular resistance and endothelial damage, due to increased production of many pro-oxidative and pro-inflammatory factors.…”
Section: Aldosterone In Pregnancy and Preeclampsiamentioning
confidence: 99%
“…T-helper 17 are a subset of CD4 T-cells producing interleukin 17, that is involved in many autoimmune diseases, such as Hashimoto's thyroiditis (20). Recently, we reported that PA patients have an increased prevalence of Hashimoto's thyroiditis (21) and an increased titer of autoantibodies against the angiotensin II type 1 receptor (AT1-AA), that could have some pathogenetic role in PA and related complications (22). From all these studies the important role of Aldo in the genesis of inflammation and related diseases seems mostly mediated by the presence of MR in MNL and macrophages.…”
mentioning
confidence: 99%